Asymmetry in the response of eastern Australia extreme rainfall to low‐frequency Pacific variability. Issue 10 (23rd May 2013) - King, Andrew D.; Alexander, Lisa V.; Donat, Markus G.
Abstract : [1] This study investigates relationships between variability in the Pacific and extreme rainfall in eastern Australia. Using an index of extreme precipitation derived from a daily gridded precipitation data set from 1900 to 2011, we find that a nonlinear relationship between El Niño–Southern Oscillation and extreme rainfall exists. That is, the strength of a La Niña episode has a much greater influence on the intensity and duration of extreme rainfall than the magnitude of an El Niño episode. This relationship is found in both interpolated observations and reanalysis data and may be explained, in part, by shifts in the divergence of moisture flux. There is significant decadal variability in the relationship, such that the asymmetry is enhanced during Interdecadal Pacific Oscillation (IPO)–negative events and is nonexistent during IPO‐positive phases. This information has the potential to be of great use in the seasonal prediction of intense rainfall events that lead to flooding. Key Points: An asymmetric relationship exists between ENSO and East Australia extreme rain The asymmetric ENSO‐extreme rainfall relationship is modulated by the IPO Large‐scale atmospheric circulation changes may explain the asymmetry